Якшур-Бодья - сердцу милый уголок: 1929-1999 / [составитель В. Н. Иванова] - Иванова Валентина Никоноровна (1999)
Экземпляры: кр (20210330) / Инвентарный номер: 30511 / Цена: / Сис.шифр: 63.3(2Рос-6Удм) / Авт.знак: Я 50 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)